The Importance of Implementing Critical Literacy in Teaching and Learning Activities for EFL Learners in Indonesia - Devi Purmayanti (Journal of Cultural Narratives in Digital Society, 2025)
This paper explores the importance of implementing critical literacy in teaching and learning activities for EFL (English as a Foreign Language) learners in Indonesia, especially in today’s digital world where misinformation spreads easily. The highlights three major benefits of critical literacy: enhancing student’s critical awareness, enabling deeper examination of texts within social and cultural contexts, and recognizing the crucial role of teacher readiness in its application. Although there are challenges—like students coming from different backgrounds and limited support for teachers—the paper suggests that with the right strategies and support, both students and teachers can benefit from bringing critical literacy into the classroom.